Prediction markets to forecast electricity demand - Luciano I. De Castro; Peter Cramton (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2009)
Forecasting electricity demand for future years is an essential step in resource planning. A common approach is for the system operator to predict future demand from the estimates of individual distribution companies. However, the predictions thus obtained may be of poor quality, since the reporting incentives are unclear. We propose a prediction market as a form of forecasting future demand for electricity. We describe how to implement a simple prediction market for continuous variables, using only contracts based on binary variables. We also discuss specific issues concerning the implementation of such a market.
Keywords: 330; forecast of electricity demand; power generation planning; implementation of prediction markets; forecast of future demand; mechanism design of capacity markets; prediction market for continuous variables; winner-takes-all contract; index contract